Adequacy of iodisation of salt at the household level and its associated factors in a rural sub-centre area of Bangalore Urban District, Karnataka, India: a cross-sectional study - Kalliath, Jacob D.; Agrawal, Twinkle; Fathima, Farah N.; Antony, Sonu; Antony, Amal; Gampala, Swarajyam; Bata, Dilip K. (International Journal Of Community Medicine And Public Health, 2019)
Background: Consumption of iodised salt is a simple, eﬀective and inexpensive preventive measure to prevent iodine deﬁciency disorders. Lack of awareness, faulty practices in storage as well as poor production quality lead to decreased availability of iodine at consumer level. The objective of the study was to estimate the proportion of households using adequately iodised salt and to assess their awareness and practices regarding iodised salt consumption in a subcentre region of Sarjapur PHC area in Bangalore Urban District. Methods: A cross-sectional study was done in 382 households selected by two stage method involving proportional allocation based on village size followed by systematic random sampling at village level. MBI salt testing kit was used to check for iodisation level. Results: Of the 382 households, 22.3% used inadequately iodised salt. Out of the 382 individuals interviewed, 72% were females and only 21% were aware about iodised salt. Majority of the households purchased salt from a general store, was stored in tightly closed plastic containers and kept on shelves. Only 5% looked for the iodine logo on the packets before purchase of salt. Individuals with poor awareness, purchase of salt at public distribution system store, storage of salt on the floor, use of crystal salt were significantly associated with presence of inadequately iodised salt at the household. Conclusions: Nearly 30% of the salt packets used by households were inadequately iodised. Awareness regarding iodised salt was poor which contributed to the presence of inadequately iodised salt at household level.